Implementasi Metode Muraja’ah Berbasis Spiker Murottal dalam Menghafal Al-Qur'an di TPQ al-Huda Binububaru Kecamatan Padang Gelugur Pasaman - Erika; Al Baihaqi Anas (YASIN, 2026)
The application of an effective repetition method is necessary to maintain, strengthen, and improve the quality of students’ Qur’an memorization. However, the implementation of muraja’ah at TPQ Al-Huda Binububaru continues to face limited time, insufficient teaching staff to monitor memorization, and inconsistent memorization practice. This study aimed to describe the implementation of the muraja’ah method using murattal recitations played through loudspeakers and to identify the factors supporting and inhibiting its implementation at TPQ Al-Huda Binububaru, Padang Gelugur Subdistrict, Pasaman. This study employed a qualitative approach with a field research design. The research informants consisted of male and female teachers and students. Data were collected through observation, interviews, and documentation and were then analyzed through data reduction, data presentation, and conclusion drawing. Data validity was established using source and technique triangulation. The findings showed that the muraja’ah method using murattal recitations played through loudspeakers was implemented through the stages of planning, implementation, and evaluation. The application of this method helped strengthen memorization, improve the accuracy of tajwid and letter articulation, enhance reading fluency, and increase students’ motivation. Its implementation was supported by students’ motivation, teacher guidance, parental support, the availability of facilities, and a regular schedule. The inhibiting factors included differences in memorization ability, low concentration, limited teacher monitoring and time, and differences in students’ reading speed. This study concludes that the muraja’ah method using murattal recitations played through loudspeakers can serve as an alternative approach to tahfiz learning for improving the quality of Qur’an memorization through structured and continuous repetition.